Designing Creative, Visual, and Adaptive Educational Media through Workshops for Elementary School Teachers to Enhance Learning Engagement in Generation Alpha (BERBAKTI : Jurnal Pengabdian Kepada Masyarakat, 2026)
This community service program aims to enhance elementary school teachers' competence in designing creative, visual, and adaptive learning media based on traditional games to improve learning engagement among Generation Alpha students. The problem identified among partner schools is the limited use of contextual and culturally relevant learning media, as well as teachers' dependence on conventional and technology-centered approaches that do not fully stimulate students' cognitive and social development. The program was conducted in collaboration between the Elementary School Teacher Education Program (PGSD) of STKIP Kusuma Negara and SD Negeri Makasar 07. The activities were carried out through training and workshops, which included: (1) fostering an imaginative culture through character education based on visual awareness, (2) material on Generation Alpha covering technology, local wisdom, and learning media, and (3) demonstrations of traditional game-based learning media. The results of the program indicate an improvement in teachers' understanding of developing creative, visual, and adaptive learning media. This is reflected in participants' ability to design and implement traditional game-based learning media within classroom learning scenarios. In addition, most participants demonstrated active engagement during the activities and were able to adapt the developed media to suit the characteristics of Generation Alpha students. Participant feedback also showed positive responses to the implementation of the program, particularly in terms of the relevance of the materials, ease of application, and its benefits in improving the quality of learning. This program also encourages teachers to integrate local cultural elements into more innovative and contextual learning practices.
Keywords: Creative learning media; Generation Alpha; Teacher training; Traditional games; Visual learning.